2020
DOI: 10.1101/gad.328575.119
|View full text |Cite
|
Sign up to set email alerts
|

Break-induced replication promotes fragile telomere formation

Abstract: TRF1 facilitates the replication of telomeric DNA in part by recruiting the BLM helicase, which can resolve G-quadruplexes on the lagging-strand template. Lagging-strand telomeres lacking TRF1 or BLM form fragile telomeres-structures that resemble common fragile sites (CFSs)-but how they are formed is not known. We report that analogous to CFSs, fragile telomeres in BLM-deficient cells involved double-strand break (DSB) formation, in this case by the SLX4/SLX1 nuclease. The DSBs were repaired by POLD3/POLD4-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 55 publications
4
61
0
Order By: Relevance
“…When barriers prevent the completion of replication, cells can activate the mitotic DNA synthesis (MiDAS) pathway to resume synthesis before cell division. Following induction of telomeric 8oxoG, we observe a robust increase in single chromatid MiDAS events, which is consistent with other models of telomere replication stress (Min et al, 2017;Özer et al, 2018;Yang et al, 2020). We verified the telomere DDR response we observed was due to DNA replication by comparing replicating cells with serum-starved quiescent cells.…”
Section: Discussionsupporting
confidence: 90%
“…When barriers prevent the completion of replication, cells can activate the mitotic DNA synthesis (MiDAS) pathway to resume synthesis before cell division. Following induction of telomeric 8oxoG, we observe a robust increase in single chromatid MiDAS events, which is consistent with other models of telomere replication stress (Min et al, 2017;Özer et al, 2018;Yang et al, 2020). We verified the telomere DDR response we observed was due to DNA replication by comparing replicating cells with serum-starved quiescent cells.…”
Section: Discussionsupporting
confidence: 90%
“…Precise molecular mechanisms leading to this latter phenotype still are only partially understood. However, recently it has been shown that DSB formation and the BIR (Break-Induced Replication) repair pathway were involved in formation of fragile telomeres ( Yang et al, 2020 ). Telomeric sister chromatid exchange could be detected by CO-FISH (Chromosome Orientation-FISH), a strand-specific variant of FISH and this phenotype is associated with telomeric replication defects ( Cherdyntseva and Gagos, 2020 ).…”
Section: Telomeric Dna Replication By the Conventional Replication Mamentioning
confidence: 99%
“…As a whole, even if TRF1 in effect protects telomeres against damage, it is more dedicated to replicating the internal telomeric tract than actually capping the telomere terminus. TRF1 and BLM, which has been shown to resolve G4 structures [93], it has been proposed that TRF1 would recognize forks blocked by the formation of these conformations on the lagging strand [13,68] and recruit BLM, although what exactly TRF1 recognizes is still unknown. The situation seems clearer for TRF2.…”
Section: The Distinct Biological Roles Of Trf1 and Trf2mentioning
confidence: 99%